2015
DOI: 10.1519/jsc.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Cardiorespiratory Responses of Pregnant and Nonpregnant Women During Resistance Exercise

Abstract: The purpose of this study was to determine cardiorespiratory responses in pregnant and nonpregnant women during the execution of resistance exercises for upper and lower body. Twenty healthy women (10 pregnant: 22-24 weeks, 25.20 ± 4.44 years, 69.80 ± 9.52 kg, 161.60 ± 5.21 cm and 10 nonpregnant: 25.20 ± 3.73 years, 62.36 ± 8.60 kg, 162.40 ± 3.97 cm) performed 5 experimental sessions. Session 1: familiarization with the equipments and the determination of 1 estimated maximum repetition. Sessions 2, 3, 4, and 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 18 publications
1
13
0
2
Order By: Relevance
“…Five of eleven national guidelines concerning exercise in pregnancy recommend resistance exercise (2). Our results show that resistance exercise in the second trimester of normotensive pregnancy does not seem to negatively impact BP, concurring with Bgeginski et al (10) who recently showed that BP response to resistance exercise was within healthy limits and significantly lower in a pregnant group than in a matched non-pregnant group. Pregnancy itself causes a decrease in BP due to reduction of peripheral vascular resistance (17), which might represent a protective effect on cardiovascular health in early to mid-pregnancy (11).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Five of eleven national guidelines concerning exercise in pregnancy recommend resistance exercise (2). Our results show that resistance exercise in the second trimester of normotensive pregnancy does not seem to negatively impact BP, concurring with Bgeginski et al (10) who recently showed that BP response to resistance exercise was within healthy limits and significantly lower in a pregnant group than in a matched non-pregnant group. Pregnancy itself causes a decrease in BP due to reduction of peripheral vascular resistance (17), which might represent a protective effect on cardiovascular health in early to mid-pregnancy (11).…”
Section: Discussionsupporting
confidence: 91%
“…Amorim et al (9) concluded that maternal BP levels were slightly increased during aerobic exercise, followed by a substantial hypotensive effect hours after the exercise session. Recently, Bgeginski et al (10) showed that BP response to resistance exercise is unaffected by pregnancy and this has been demonstrated to remain within safe margins during exercise. Finkelstein et al (11) concluded that there was no difference in cardiovascular response between pregnant and nonpregnant women during land or water exercise, although BP response was lower during exercise in water.…”
Section: Key Messagementioning
confidence: 99%
See 1 more Smart Citation
“…Our results show that the combination of aerobic and resistance exercise in both the second and third trimesters of pregnancy does not induce unsafe changes in blood pressure. Furthermore, Bgeginski et al reported that blood pressure, together with FHR, stayed within normal limits during resistance exercise in pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…The exercise protocol has been published previously 14 . The muscles mainly activated during the exercise in the bilateral leg extension are the quadriceps femoris, and during the exercise in the pec-deck fly, the pectoralis major and anterior deltoid muscles are activated.…”
Section: Methodsmentioning
confidence: 99%